Konservasi Penyu Di Pantai Pasi Jalang, Lhoknga, Kabupaten Aceh Besar - Anita Rauzana; Lenni Fitri; Yekki Yasmin; Suwarno; Wira Dharma (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Lhoknga beach area is one of the areas in Aceh that has beautiful beaches and enormous potential for marine wealth, including turtles. This area is a paradise for turtles to lay their eggs. Turtles are reptiles living in the sea and whose existence has long been threatened by nature and human activities. Internationally, sea turtles are included in the 'red list' in the International Union for Conservation of Nature and Natural Resources (IUCN), which means that their existence in nature is threatened with extinction, so all forms of utilization and distribution must receive serious attention. Therefore, turtle conservation efforts are an essential and urgent program to protect and save turtle populations, especially in Indonesia because, in Indonesia, there are 6 out of 7 turtle species that still exist today. This activity has been completed at Lhoknga Beach by releasing 120 turtle hatchlings. It is hoped that this community service activity will be able to increase public awareness to participate together in preserving turtles and not hunting them anymore.